Endocervical adenocarcinomas and HPV genotyping in an HIV endemic milieu – a retrospective study - Lovane, Lucília; Larsson, Gabriella Lillsunde; Tulsidás, Satish; Carrilho, Carla; Andersson, Sören; Karlsson, Christina (BMC women's health, 2025)
Background Cervical cancer is the most prevalent cancer in Mozambique, with endocervical adenocarcinoma accounting for approximately 5.5% of cases. Knowledge regarding the most prevalent HPV genotypes in endocervical adenocarcinoma is limited, within this setting. This study aimed to investigate human papillomavirus (HPV) prevalence and genotypes within a cohort of endocervical adenocarcinoma patients in the context of Mozambique’s recently introduced vaccination programme, considering the country's HIV-endemic setting. Methods Forty consecutive cases of endocervical adenocarcinoma diagnosed at Maputo Central Hospital between 2017 and 2018, with limited clinical data available, were included. Human immunodeficiency virus (HIV) status was determined through serological data or in situ hybridisation on histopathological slides. HPV detection was performed using a multi-methodological approach, including Anyplex II, in-house polymerase chain reaction (PCR), and chromogenic and fluorescent in situ hybridisation techniques. Results All 40 cases exhibited HPV-dependent morphology. Fourteen of the 40 patients were HIV-positive. No significant differences were observed between the two groups regarding age, stage, or histopathological type. hrHPV16, 18, or 45 were detected in all cases. Notably, multiple hrHPV infections were identified exclusively in HIV-negative cases (10/26, p = 0.0075), with hrHPV18/45 co-infection being the most common ( n = 8). Conclusions These findings suggest that the newly implemented quadrivalent vaccination programme has the potential to prevent morbidity and mortality from endocervical adenocarcinoma, irrespective of HIV infection status, in Mozambique's HIV-endemic environment.